Erectile Dysfunction Can be Successfully Treated with Natural Remedies - Doepp, Manfred (British Journal of Healthcare and Medical Research, 2025)
Unquestionably the incidence of erectile dysfunction is increasing, even among younger men. In parallel, the number of sperm in ejaculations is decreasing, as is the number of births in first world countries. All this has intensified since the years of the Covid 19 pandemia. Understandably, the use of chemical agents such as sildenafil has increased. It is therefore advisable to be able to resort to natural remedies to counteract these developments. Here we present a combination of nine natural remedies from East Asia that together can offer a solution to these problems. These also have the effect of reducing an enlarged prostate in older men. Incidentally, we also found that there was an increase in blood flow to the user’s central nervous system.